Plant-source foods: Leveraging crops for nutrition and healthy diets - Boy, Erick; Brouwer, Inge D.; Foley, Jennifer; Palacios, Natalia; Scott, Samuel P.; Taleon, Victor (International Food Policy Research Institute, 2024)
Addressing the urgent need for food systems to support sustainable healthy diets will require a major improvement in the availability of and access to affordable, nutritious foods such as fruits, vegetables, and whole grains in low- and middle-income countries, along with increased consumer demand for healthy diets. Plant-source foods are key components of sustainable healthy diets. This chapter examines food crops that could be leveraged to improve health outcomes, describes production systems and their role in providing populations access to highly nutritious crops, and presents examples of evidence-based technologies that improve the nutritional content of crops, especially for vulnerable populations.